Language ideologies in the mirror of some Serbian students’ attitudes towards variation and change in British English - Svetlana R. Stojić (University of Belgrade, 2017)
Popular beliefs and value judgements about language underlie attitudes that may reflect various language ideologies. In this light, the paper presents some results of two questionnaire-based surveys into students’ overt attitudes towards varieties of English. The first survey was carried out in 1997 amongst first-year students of English at the English Department of the Faculty of Philology, Belgrade University, while a replication survey was conducted in 2016. The primary aim of this comparative study is to assess whether any ideological and attitudinal shifts may have occurred in the intervening nineteen years. The main focus of this paper is on the results related to attitudes towards varieties of British English and towards language change. The comparison of the results has indicated that, although a lower percentage of the 2016 survey respondents expressed stereotypical views of some social and regional varieties of British English, their attitudes towards language change are very similar to those expressed by the participants in the 1997 survey.